Regjeringsmakt og motstandspolitikk - Asdal, Kristin (Tidsskrift for kulturforskning, 2004)
In the last few years the tradition of science studies has started to turn "outwards" and engage in empirical studies of politics. This article is part of this movement. I present a cluster of selected stories to show how a specific form of governable nature was created in a particular set of scientific and technical practices. Through these stories I show how a new governable entity called "fluorine" altered established policies in Norway. I also show that this material entity "fluorine" became governable because it was quantified. This quantification helped to create "political fluorine" as a crucial object in real political events. Thus, the article is on the significance of numerical technologies in the making of the political. However, the politics of nature and its objects, come into being (or not) when they encounter other entities, such as the factory or "the economy". The ambition of this is article is to demonstrate the ways in which these clashes or confrontations help to shape both a state politics and a politics of resistance.